Plant macrofossils, ichnofossils, facies analysis and palaeoenvironment interpretation of the Hojedk Formation in the north of Kerman (Central Iran) - Hadis Khalilizadeh; Abbas Ghaderi; Ali Reza Ashouri; Hamed Zand-Moghadam (Journal of Stratigraphy and Sedimentology Researches, 2019)
Abstract This study led to identify 30 species and 16 genera of eight different plant macrofossils orders including Equisetales, Cycadales, Bennettitales, Coniferales, Peltaspermales, Ginkgoales, Corystospermales, and Filicales at the Deh-Shiykh section, north of Kerman. According to stratigraphic ranges of the index taxa such as Otozamites furoni, Nilssoniopteris mosafolia, Nilssonia tenuicaulis, Anomozamites major, Coniopteris hymenophylloides, Nilssonia bozorga and Elatides thomasii the age of early Middle Jurassic (Bajocian–Bathonian) is assigned to the Deh-Shiykh section. Middle Jurassic ichno fossils of the Hojedk Formation in the Deh-Sheikh section have been studied for the first time. The study also led to the determination of terrestrial ichno fossils including eight ichno species, belonging to four ichnogenera such as Planolithes, Rhizoliths, Taenidium and Thalassinoides. They have been found alongside the stems of Equisetals. Combination of the results of ichno fossil studies with plant fossils help us to identify the palaeoenvironment. These plant fossils are generally indicator of humid conditions. Moreover, the identified ichnofossils in accordance with the sedimentological studies, represent deltaic environments influenced by the river systems and channels. This is the first study of the combination of three studies of paleontology (Plant macrofossils), sedimentology and ichnology in east central Iran. The results have contributed to the accurate understanding of the paleoenvironment of fossiliferous horizons of the Hojedk Formation. Keywords: Plant macrofossils, Tracefossils, Middle Jurassic, Delta, Kerman.